Taxonomic status of Cacoplox griseatus Hull, 1970 with redescription of the genus and type species (Diptera, Bombyliidae, Bombyliinae, Bombyliini) - Lopes, Daniele De Araujo; Lamas, Carlos José Einicker (Zootaxa, 2004)
The taxonomic status of the monobasic genus Cacoplox Hull, 1970 is discussed and confirmed after comparison with species of Notoschistus Bowden, 1985. The genotype and the type species C. griseatus Hull, 1970 are redescribed. An identification key to separate these two genera is also presented. Cacoplox griseatus is recorded for the first time from Argentina. It was previously known only from Chile, always at altitudes higher than 3,000 meters.